3D transient heat transfer numerical analysis of multiple energy piles - Cui, Yuanlong; Zhu, Jie (Elsevier, 2017)
This paper presents a three-dimensional (3D) transient heat transfer numerical model for multiple energy piles based on the finite volume method (FVM). The initial and boundary conditions are established and the effects of “thermal short-circulating” between two pipes of a U-tube in energy pile are investigated. Thermal partial differential equations are discretized at the spatial nodal points and solved by linear approximation method. Temperature variations of working fluid, energy pile and its surrounding soil from simulation program are compared with experimental data to validate the developed model. In addition, the influences of fluid flow rate and U-tube shank spacing are analysed. It is established that the shank spacing should be set in a range of 0.06m to 0.10m to reduce heat transfer between the two pipes and meet the structural requirement. Meanwhile, the flow rate should be controlled in a range of 0.5m3/h to 0.7m3/h to avoid the low outlet fluid temperature and decrease the influence of “thermal short-circuiting”.